2020
DOI: 10.1186/s12933-020-01054-z
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-glucose index predicts adverse cardiovascular events in patients with diabetes and acute coronary syndrome

Abstract: Background: The triglyceride-glucose index (TyG index) has been regarded as a reliable alternative marker of insulin resistance and an independent predictor of cardiovascular outcomes. Whether the TyG index predicts adverse cardiovascular events in patients with diabetes and acute coronary syndrome (ACS) remains uncertain. The aim of this study was to investigate the prognostic value of the TyG index in patients with diabetes and ACS. Methods: A total of 2531 consecutive patients with diabetes who underwent co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
209
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(228 citation statements)
references
References 41 publications
18
209
1
Order By: Relevance
“…[6,18,19] Wang et al reported the TyG index predicted future cardiovascular events in patients with diabetes and acute coronary syndrome independently of known cardiovascular risk factors. [7] However, in a previous study based on a Caucasian population, the TyG index displayed an insigni cant association with stroke. [20] Later, another study based on the same Caucasian cohort, identi ed metabolic health and obesity states groups based on TyG index was signi cantly associated with the risk of IS.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…[6,18,19] Wang et al reported the TyG index predicted future cardiovascular events in patients with diabetes and acute coronary syndrome independently of known cardiovascular risk factors. [7] However, in a previous study based on a Caucasian population, the TyG index displayed an insigni cant association with stroke. [20] Later, another study based on the same Caucasian cohort, identi ed metabolic health and obesity states groups based on TyG index was signi cantly associated with the risk of IS.…”
Section: Discussionmentioning
confidence: 86%
“…[5] Previous studies have indicated that the TyG index is associated with cardiovascular disease morbidity and mortality in the general population and different types of patient cohorts. [6][7][8][9] Lately, the TyG index has been proposed as a direct marker for the risk of incident ischemic stroke (IS) in general population. [10] To date, no relevant study has focused on the impact of the TyG index on mortality in patients with critically ill stroke including IS and hemorrhage stroke (HS).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies about the TyG index in predicting CVEs in patients with ACS complicated with T 2 DM have been published in succession. Wang et al followed up 2,531 ACS patients with T 2 DM for 3 years and found that the incidence of MACEs increased with the increase of TyG index, the TyG index was an independent predictor of MACEs, and the optimal TyG index cut-off for predicting MACEs was 9.323 [24] . A study by Ma et al of 776 patients with T 2 DM and ACS who underwent PCI also showed that the TyG index was signi cantly associated with adverse CV outcomes, including all-cause mortality, non-fatal stroke, nonfatal MI and unplanned repeat revascularization [23] .…”
Section: Discussionmentioning
confidence: 99%
“…The TyG index was regarded as a reproducible, reliable, and valid surrogate marker of IR [12,14,15] . Numerous studies have indicated that the TyG index was signi cantly correlated with the occurrence of CVDs and poor CV prognosis [16][17][18][19][20][21][22][23][24][25] . However, no previous study has exclusively investigated the predictive value of the TyG index for adverse CVEs in AMI patients with T 2 DM.…”
Section: Introductionmentioning
confidence: 99%
“…Among the traditional risk factors, levels of fasting plasma glucose (FPG) and triglycerides (TG) are associated with an increased risk of type 2 diabetes mellitus (T2DM) [2,[9][10][11]. As a derivative of FPG and TG [12][13][14], the triglycerides-glucose (TyG) index seems to help better predict the risk of T2DM than either component factor and has recently been suggested as a predictor of this risk in individuals without diabetes [2,8,[15][16][17]. The TyG index was suggested to be considered as a screening tool for identifying people at a high risk of T2DM in clinical practice [18].…”
Section: Background/introductionmentioning
confidence: 99%